Assessment of Medication Adherence in Saudi Patients With Type II Diabetes Mellitus in Khobar City, Saudi Arabia - AlQarni, Khaled; AlQarni, Elham A.; Naqvi, Atta Abbas; AlShayban, Dhfer Mahdi; Ghori, Syed Azizullah; Haseeb, Abdul; Raafat, Mohamed; Jamshed, Shazia (Frontiers in Pharmacology, 2019)
Objective Medication adherence is defined as taking medications as advised and prescribed by health care professionals for stated duration. Diabetes mellitus (DM) is one of the most common chronic illnesses in Saudi Arabia. This study aimed to document medication adherence in Saudi patients with type 2 diabetes. Methods A quantitative cross-sectional study was conducted in Saudi out-patients with type 2 diabetes mellitus in the city of Khobar, Saudi Arabia. The study used the General Medication Adherence Scale (GMAS) to document medication adherence in this population. Data was analyzed through SPSS version 23. Study was ethically approved. Results Data was collected from 212 patients. Few patients (35.8%) had high adherence to anti diabetic medications. The correlation between HbA1c level and adherence score was negative and significantly strong (ρ = -0.413, p<0.0001). Most patients (N = 126, 59.4%) modified their medication therapy in religious events such as Ramadan and Eid. Education level was not a determinant of adherence in this population. Conclusion This study highlighted that medication adherence is influenced by religious and social factors. Patient counseling is required to improve patient beliefs and increase awareness of adhering to prescribed anti diabetic pharmacotherapy. A pharmacist can play constructive role of a disease educator and patient counselor.